Mobile App for Incubator Monitoring to Optimize Quail Egg Production - Agus Nur Khomarudin; Indra Farhan; Rabby Nazli; Rina Novita; Romy Aulia; Sholihah Ayu Wulandari (Jurnal Teknologi Informasi dan Terapan, 2026)
Incubation is a crucial process in egg hatching, where eggs must be maintained under optimal temperature and humidity conditions. To ensure the stability of these parameters, a monitoring system is needed one that operates continuously, provides sufficient accuracy, and is easily accessible to users. This study aims to design a Mobile Application for Monitoring Temperature and Humidity in Quail Egg Incubators that is both valid and effective, as a means to enhance and optimize quail egg production. The research follows the Agile Method, consisting of the following phases: Plan, Design, Develop, Test, Deploy, Review, and Launch. The Mobile App for Incubator Monitoring to Optimize Quail Egg Production underwent product testing, including a validity test conducted by several experts in computer and mobile applications. The test resulted in a score of 0.78, which falls into the valid category. The effectiveness test yielded a score of 0.35, indicating a moderate level of effectiveness. The implementation of this monitoring application has shown a significant positive impact on operational efficiency in quail farming, particularly at Nisya Farm. User experience was evaluated through direct observation and interviews with respondents. Overall, users reported that the app is easy to use, thanks to its simple and intuitive interface. User feedback strengthens the argument that technological integration not only brings technical benefits but also boosts farmers’ confidence in managing the incubation process. This is essential, as the success of technology adoption heavily depends on how comfortable and user-friendly it is for its intended users.